2019
DOI: 10.25105/imar.v17i1.4663
|View full text |Cite
|
Sign up to set email alerts
|

Analysis the Impact of Liquidity, Profitability, Activity and Solvency Ratio on Change in Earnings

Abstract: <p class="Imar-Abstract">This study aims to determine the impact of liquidity, profitability, solvency, and activity ratio on change in earnings. In this research, multiple linear regression is used to identify a change in earnings on an entity. The sample data are taken from consumer goods of manufacturing company listed on BEI for the period 2014-2017. The results of this study show net profit margin as profitability ratio have a significant effect on change in earnings. The other results show liquidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 1 publication
1
9
0
4
Order By: Relevance
“…Based on a theoretical explanation and supported by previous research, the first hypothesis is formulated as follows: H1: Sales growth has a positive effect on profit changes 2.3. The Effect of Profitability on Changes in Profit Baraja & Yosya (2018) explained that profitability is a ratio to calculate the firm's business performance for creating income on balance sheet assets, operating costs, and income each time. In addition, it provides parameters for the level of effectiveness of the company's management.…”
Section: Effect Of Sales Growth On Changes In Profitmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a theoretical explanation and supported by previous research, the first hypothesis is formulated as follows: H1: Sales growth has a positive effect on profit changes 2.3. The Effect of Profitability on Changes in Profit Baraja & Yosya (2018) explained that profitability is a ratio to calculate the firm's business performance for creating income on balance sheet assets, operating costs, and income each time. In addition, it provides parameters for the level of effectiveness of the company's management.…”
Section: Effect Of Sales Growth On Changes In Profitmentioning
confidence: 99%
“…Change in Profit (Y) H3: Dividend policy has a positive effect on profits changes 2.5. Effect of Liquidity on Changes in Profit Baraja & Yosya (2018) revealed that liquidity is a ratio that illustrates the firm's performance and resolves short-term obligations. The function of liquidity reveals the firm's capability to fulfill its maturing bonds, such as obligations to parties inside or outside the company.…”
Section: Effect Of Sales Growth On Changes In Profitmentioning
confidence: 99%
“…The definition of 'liquidity' is used to address the company's financial situation. In accordance with Kasmir (2012), the purpose of such ratio is to illustrate or calculate the ability of the company to satisfy due obligations, both to parties outside the company and within the company (as cited in Baraja & Yosya, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Capital structure variables are considered as dependent one and they are represented by debt-equity ratio (Mallikarjunappa & Goveas, 2007;(Sathyanarayana et., al., 2017;Baraja & Yosya, 2018) and debt-asset ratio (Margaretha & Fitrah, 2012;(M'ng et al, 2017;Amraoui et al, 2018) Debt-Equity Ratio = Total Debt Equity Debt-Asset Ratio = Total Debt Total Asset…”
Section: Dependent Variablesmentioning
confidence: 99%
“…It is aimed to provide for sufficient funds for fulfilling current liabilities without restoring external financing. Current study uses ratio of current assets to current liabilities as proxy of liquidity (Rani et al, 2016;Amraoui et al, 2018;Baraja & Yosya, 2018)…”
Section: Liquidity (Liq)mentioning
confidence: 99%